2019
DOI: 10.1002/jhet.3493
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Docking, and Anticancer Activity of New Thiazole Clubbed Thiophene, Pyridine, or Chromene Scaffolds

Abstract: 2‐Cyanoacetamido‐4‐methylthiazole (1) was utilized as a versatile precursor for the construction of new thiazole clubbed thiazolidine, thiophene, pyridine, or chromene scaffold. The base‐catalyzed addition of 1 to phenyl isothiocyanate followed by subsequent treatment of the produced thiocarbamoyl intermediate with ethyl chloroacetate or chloroacetonitrile furnished the corresponding thiazolyl‐thiazolidine and thiazolyl‐thiophene hybrids. The reactions of compound 1 with chemical reagents, namely, acetylaceton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Heating of compound 38 with 29a,b or 24a in DMF/EtOH at reflux in the presence of triethylamine, resulted in the formation of 5-acetyl(or-benzoyl)-4-amino-2-phenylaminothiophene-3carboxamides 39a-c (Scheme 16). 80,81…”
Section: Scheme 15mentioning
confidence: 99%
“…Heating of compound 38 with 29a,b or 24a in DMF/EtOH at reflux in the presence of triethylamine, resulted in the formation of 5-acetyl(or-benzoyl)-4-amino-2-phenylaminothiophene-3carboxamides 39a-c (Scheme 16). 80,81…”
Section: Scheme 15mentioning
confidence: 99%
“…MOE builder tool was used in building the ligand structures. Next, the correct atom types (including hybridization states) and correction of the bond types were defined, hydrogen atoms were added, charges were assigned to each atom, and then the structures were subject to energy minimization using AMBER10:EHT method until a gradient of 0.01 was reached, this process was applied for co-crystallographic or the ligand structures [31,32].…”
Section: Preparation Of the Ligandmentioning
confidence: 99%
“…Over the last several years, hybrid drug design has been used as a prime method for developing novel anticancer therapies that can solve many of the pharmacokinetic disadvantages of traditional anticancer drugs. Thus, several studies have indicated that thiazole–thiophene hybrids have important anticancer activity [ 24 ].…”
Section: Introductionmentioning
confidence: 99%